CEO Power on Earnings Management and the Role of Earnings Targets: A Proposed Research Framework - TONOY ROY,; MAZNI ABDULLAH,; ERVINA ALFAN, (Asian Journal of Accounting Perspectives, 2024)
Research aim: This paper aims to present a conceptual framework for CEOs that abuse their power to manage earnings, and the pressure of attaining earnings targets moderating the effect of this power abuse on earnings management (EM). Design/ Methodology/ Approach: To develop the proposed conceptual framework, this study performed a comprehensive literature review consisting of theoretical discussions and comparative arguments. The development of the framework also involved analysing and summarising the contributions, limitations, and suggestions from previous studies. Following this approach, the conceptual framework was built addressing issues related to CEO power, EM, and earnings targets. Research finding: Based on the propositions, the proposed research framework expects a significant positive effect of CEO power on EM, and that the pressure of attaining earnings targets will significantly moderate the CEO power and EM nexus among Malaysian listed firms. Malaysian CEOs with more power are expected to manage earnings more easily, and the pressure of attaining earnings targets is expected to influence powerful CEOs to manage earnings. Theoretical contribution/ Originality: The proposed conceptual framework adds new perspectives to the existing literature by explaining the linkages between CEO power, earnings targets, and EM based on agency theory and upper echelons theory. Moreover, the harmonisation between the Type I agency problem and upper echelons theory is a novel contribution. The framework highlights the influence of the pressure of earnings targets on powerful CEOs’ EM practices. Moreover, two conditions for considering the effect of earnings targets are proposed. Practitioner/ Policy implication: Malaysian audit firms and listed companies can shape their accounting and monitoring strategies based on the eight formulated propositions. Moreover, this paper will also enable Malaysian regulators and standard setters to revise the existing Malaysian Code on Corporate Governance (MCCG). Research limitation: This is only a conceptual paper that requires an empirical study with quantitative data to test the propositions and validate the proposed conceptual framework. Hence, the anticipated practical implications are subjected to future empirical validation. Keywords: CEO power, Earnings management, Earnings target, Agency theory, Upper echelons theory Type of article: Conceptual paper JEL Classification: M12, M41